Noir : the romance of black in 19th-century French drawings and prints - Hendrix, Lee; J. Paul Getty Museum (Los Angeles : J. Paul Getty Museum, 2016)
"Accompanies an exhibition at the Getty Center in Los Angeles and explores tonality and black media in nineteenth-century French drawings and prints"--Provided by publisher.
Revivals and modernity: the printed image in nineteenth-century France / Cynthia Burlingham -- Prelude: dark romanticism / Lee Hendrix -- Landscape, charcoal, and the etching revival / Lee Hendrix -- Realism / Lee Hendrix -- Fantasy and dreams / Lee Hendrix -- The optics of shadow / Lee Hendrix -- Diversity and complexity in black drawing media: four case studies / Michelle Sullivan and Nancy Yocco -- Dessin au fusain: nineteenth-century French charcoal drawing materials and techniques / Timothy David Mayhew -- A closer look: an illustrated glossary of materials and techniques used in nineteenth-century noir drawings / Michelle Sullivan and Nancy Yocco.
"This publication is issued on the occasion of the exhibition Noir: The Romance of Black in Nineteenth-Century French Drawings and Prints, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from February 9 to May 15, 2016"--ECIP data view.
Includes bibliographical references (pages 164-169) and index.
Keywords: Drawing, French -- 19th century -- Exhibitions; Prints, French -- 19th century -- Exhibitions